2003
DOI: 10.2165/00139709-200322030-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oximes in the Management of Organophosphorus Pesticide Poisoning

Abstract: The number of intoxications with organophosphorus pesticides (OPs) is estimated at some 3,000,000 per year, and the number of deaths and casualties some 300,000 per year. OPs act primarily by inhibiting acetylcholinesterase (AChE), thereby allowing acetylcholine to accumulate at cholinergic synapses, disturbing transmission at parasympathetic nerve endings, sympathetic ganglia, neuromuscular endplates and certain CNS regions. Atropine is the mainstay of treatment of effects mediated by muscarine sensitive rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
324
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 406 publications
(336 citation statements)
references
References 133 publications
4
324
0
8
Order By: Relevance
“…Plasma was separated from an EDTA blood sample and frozen at -20°C. BuChE activity was assayed as described (30,31). The median (IQR) BuChE activity in this population is 4,500 (3,200) mU/mL (Eyer, unpublished).…”
Section: Hypotension In Severe Dimethoate Self-poisoning 881mentioning
confidence: 99%
“…Plasma was separated from an EDTA blood sample and frozen at -20°C. BuChE activity was assayed as described (30,31). The median (IQR) BuChE activity in this population is 4,500 (3,200) mU/mL (Eyer, unpublished).…”
Section: Hypotension In Severe Dimethoate Self-poisoning 881mentioning
confidence: 99%
“…Atropine, a muscarinic receptor antagonist, blocks cholinergic parasympathetic neurons to maintain capacity for respiration, and is typically administered as soon as possible after an OP exposure (11). Oxime reactivators like pralidoxime (2-PAM) or the Hagedom oxime HI-6 are also typically provided in an attempt to recover AcChE activity (12). Finally, an anticonvulsant like diazepam is commonly administered to treat seizures that can develop, albeit via unknown mechanisms (13).…”
mentioning
confidence: 99%
“…The treatment regimen with oximes must be rigorously followed in order to maximize the antidote effects, although there are still many doubts about the adequate regimen under certain conditions. 172 Nowadays, it is still discussed even the need of administration of oximes to victims of OPCs intoxication. [173][174][175] Studies have shown that, to be an effective AChE reactivator, a compound should possess some structural properties: it should have a quaternary nitrogen atom, which guides the molecule to the active site by interacting with the anionic subsite.…”
Section: Treatment and Antidotes For Nerve Agentsmentioning
confidence: 99%